2007
DOI: 10.1186/1472-6963-7-47
|View full text |Cite
|
Sign up to set email alerts
|

Interventions aimed at reducing problems in adult patients discharged from hospital to home: a systematic meta-review

Abstract: Background: Many patients encounter a variety of problems after discharge from hospital and many discharge (planning and support) interventions have been developed and studied. These primary studies have already been synthesized in several literature reviews with conflicting conclusions. We therefore set out a systematic review of the reviews examining discharge interventions. The objective was to synthesize the evidence presented in literature on the effectiveness of interventions aimed to reduce post-dischar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
168
1
8

Year Published

2009
2009
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 174 publications
(179 citation statements)
references
References 95 publications
2
168
1
8
Order By: Relevance
“…First, because we found high ER use immediately following discharge, interventions focused on enhancing discharge planning in obstetrics populations may reduce ER visits and hospital readmissions, as seen in nonobstetrics populations. [49][50][51][52] Studies of ''intensive discharge planning'' using the Perceived Readiness for Discharge after Birth scale have shown that the scale predicts risk of post discharge problems. 53 Use of this scale could aid in targeting those at high risk post discharge, allowing for intensive intervention to potentially decrease postpartum ER utilization.…”
Section: Commentsmentioning
confidence: 99%
“…First, because we found high ER use immediately following discharge, interventions focused on enhancing discharge planning in obstetrics populations may reduce ER visits and hospital readmissions, as seen in nonobstetrics populations. [49][50][51][52] Studies of ''intensive discharge planning'' using the Perceived Readiness for Discharge after Birth scale have shown that the scale predicts risk of post discharge problems. 53 Use of this scale could aid in targeting those at high risk post discharge, allowing for intensive intervention to potentially decrease postpartum ER utilization.…”
Section: Commentsmentioning
confidence: 99%
“…The service was provided by Harrow Social Services trained care attendants incorporating the rehabilitation ethos. 2 Like Shalchi et al, we found that common medical diagnoses at the initial episode were cardiorespiratory, but that readmission was reduced in the care attendant group. Likewise, older patients were more likely to be readmitted as emergencies.…”
Section: Alcohol and Hospital Readmission (3)mentioning
confidence: 53%
“…2,3 We read with interest Woodard and Conroy's description of an acute frailty unit, which will likely improve the standard of care provided to older patients, and we await with further data from their experience.…”
Section: In Response -Additional Support To High-risk Patients Can Rementioning
confidence: 99%
“…Una revisión de The Cochrane Library mostró que un plan de alta estructurado adaptado a cada caso reduce discretamente las estadías hospitalarias (-0,91; IC de 95% = -1,55 a -0,27) y los reingresos en adultos mayores con patología médica (RR 0,85; IC de 95% = 0,74-0,97) 49 . Mistiaen concluyó que las intervenciones que pueden tener un impacto positivo en la reducción de los problemas post alta en adultos, son aquéllas con componentes educativos, y las que combinan intervenciones pre y post alta 50 . Evans demostró que la planificación del alta desde el día 3 en pacientes de alto riesgo aumenta la probabilidad de regreso a casa (y no a una institución) (p = 0,05), y disminuye el riesgo de reingreso a 30 días (p = 0,001) 51 .…”
Section: Planificación Del Altaunclassified